Desain Pola Parkir Sepeda Motor dengan Pendekatan Ergonomi Partisipatori - Bambang Suhardi; Pringgo Widyo Laksono; Akbar Aditya Nugraha (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2017)
Motorcycle parking area in the Faculty of Engineering UNS is 2895 m2 which is divided into 5 sectors. Problems arising in the parking lot as follows: irregular parking position, the distance between motorcycles too close, the user is difficult to remove a motorcycle, and motorcycles parked carelessly in the parking circulation path. To overcome this problem parking needs to be designed parking pattern using participatory ergonomic approach. The results showed that the optimal parking pattern in terms of capacity is a parking pattern with 900 angles. Parking patterns with 900 angle can accommodate 1046 motorcycle.